2014
DOI: 10.1002/cssc.201301152
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrathin Metal Fluoride Layer in Organic Photovoltaic Cells: Mechanism of Efficiency and Lifetime Enhancement

Abstract: Although rapid progress has been made recently in bulk heterojunction organic solar cells, systematic studies on an ultrathin interfacial layer at the electron extraction contact have not been conducted in detail, which is important to improve both the device efficiency and the lifetime. We find that an ultrathin BaF2 layer at the electron extraction contact strongly influences the open-circuit voltage (Voc ) as the nanomorphology evolves with increasing BaF2 thickness. A vacuum-deposited ultrathin BaF2 layer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…Rather, an energy level offset between the electrode Fermi level and the semiconductor transport orbital is the relevant parameter, which often does not follow what the simple Mott-Schottky rule dictates. [ 40 ] Adv. Mater.…”
Section: Energetic Effect: Fermi-level Shiftmentioning
confidence: 98%
“…Rather, an energy level offset between the electrode Fermi level and the semiconductor transport orbital is the relevant parameter, which often does not follow what the simple Mott-Schottky rule dictates. [ 40 ] Adv. Mater.…”
Section: Energetic Effect: Fermi-level Shiftmentioning
confidence: 98%
“…As the applied voltage increased, the capacitance tended to increase to a peak and then decrease. The V bi is correlated with the voltage V peak at the peak capacitance as [26,27] (1)…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the energy barrier between the cathode and active layer decreases, and electrons move efficiently owing to the tunneling effects [16][17][18]. Lee et al [16] reported the improvement of the efficiency from 2.1% to 4.0% for a poly(3-hexylthiophene) (P3HT): [6,6]-phenyl C 61 butyric acid Inverted solar cells Tunneling effect Dipole layer Metal fluoride A B S T R A C T Metal fluorides (e.g., LiF and BaF 2 ) are usually introduced as an electron transport layer in conventional polymer solar cells (PSCs). However, because they are insoluble, vacuum deposition is inevitable, resulting in a high process cost and the difficulty of introduction in PSCs.…”
Section: Introductionmentioning
confidence: 99%